Diagnostic challenge in a cystic lesion of the epigastrium: A case report - Hayati F.; Azizan N.; Ariffin A.C.; Kiang K.F.; Zuhdi Z.; Jarmin R. (Gazi Universitesi, 2024)
A diagnosis of cystic lesion of epigastrium is challenging without strong evidence from history and physical examination. A 33-year-old lady has an epigastric mass without hepato-pancreaticobiliary symptoms, was unable to be diagnosed through radiological assessment and biochemical markers. She was diagnosed with hepatobiliary cystadenoma through intraoperative assessment. We present a case of biliary cystadenoma with diagnostic challenge. Copyright 2018 by Gazi University Medical Faculty.